The direct and spillover effects of diabetes diagnosis on lifestyle behaviours - Thomas, R; Mentzakis, E (Wiley, 2024)
Using blood sample data we exploit an arbitrary cut-off of diabetes risk and through a fuzzy regression kink design we estimate the effect of a diabetes diagnosis on own and partner health-related behaviours. Diabetes diagnosis increases the probability of exercising, both for those diagnosed with diabetes and their partner. We also conduct mediation analysis which suggests that joint household participation is the channel behind this effect. Our results have significant implications for the understanding of the channels that induce behavioural change, and household decision making, as well as, for the evaluation of diabetes related policies.